Unitary coupled-cluster approach for the calculation of core-excited states and x-ray absorption spectra - Thielen, Sebastian M.; Hodecker, Manuel; Piazolo, Julia; Rehn, Dirk R.; Dreuw, Andreas (The journal of chemical physics, 2021)
In this work, we present the core-valence separation (CVS) approximation applied to unitary coupled-cluster (UCC) theory for the calculation of core-excited states and the simulation of x-ray absorption spectroscopy (XAS). Excitation energies and oscillator strengths of small- to medium-sized organic molecules have been computed using the second-order and extended second-order UCC schemes (CVS-UCC2 and CVS-UCC2-x) as well as the third-order scheme (CVS-UCC3). All results are compared to the corresponding algebraic-diagrammatic construction methods and experimental data. The agreement between CVS-UCC and experimental data demonstrates its potential as a new approach for the calculation of XAS.
Gesehen am 20.05.2021